Peran Pondok Pesantren Darul Ulum As’adiyah Tokare Terhadap Kualitas Pendidikan Masyarakat Kessing - Rudhi, Rudhi; Nurdin, Nurdin; Herianti, Herianti; Aryonsyah, Ahmad; Hikmah, Andi Nurul; Irnawati, Irnawati; Ramadhani, Muhammad Fitra; Nasruddin, Muh.; Azizah, Nur Waviq; Amanda, Putri; Fajar, Rahmat (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service program is motivated by the critical role of Islamic educational institutions in improving the quality of human resources, particularly in rural areas with limited access to quality formal education. The primary focus of this community service program is the strategic role of Islamic boarding schools (pesantren) in influencing the quality of education and religious understanding of the surrounding community. The objective of this activity is to describe the role of the Darul Ulum As'adiyah Tokare Islamic Boarding School in improving the quality of education in the Kessing Village community, Soppeng Regency, and to identify the types of development activities carried out. The study employed a qualitative descriptive method, with data collection techniques including observation, in-depth interviews with the boarding school administrators and community leaders, and documentation of activities. The results of the community service program indicate that the Darul Ulum As'adiyah Tokare Islamic Boarding School plays a crucial role through three main pillars: non-formal education (majelis taklim and pengajian), ongoing moral development, and socio-religious integration. Intense interaction between the boarding school and the community has increased public awareness of education and improved the quality of religious understanding and social behavior in Kessing Village. This community service contribution provides a model for strengthening synergy between Islamic boarding schools and local communities in an effort to accelerate the quality of education based on local wisdom and religiosity at the rural level.